Theoretical analyses of a new two-stage absorption-transcritical hybrid refrigeration system. (August 2015) - He, Y.J.; Jiang, Y.Y.; Gao, N.; Chen, G.M.; Tang, L.M.
Abstract: In this context, a two-stage absorption-transcritical hybrid refrigeration system is proposed. R744 is chosen as a refrigerant for the transcritical heat pump subsystem and LiBr-H2 O working pair for the two-stage absorption refrigeration subsystem. Based on the mathematical and physical models, theoretical investigation is carried out on its performance. The main effects are discussed on COP net (the ratio of cooling capacity powered by low-grade heat to the low-grade heat consumption for the hybrid system) and COP mt (the ratio of cooling capacity powered by mechanical work to the mechanical work consumption for the hybrid system). Comparing with the normal two-stage absorption refrigeration system, theoretical results show that COP net could be improved up to about 55% when the refrigeration temperature is 7 °C. In addition, COP mt are more than 50% higher than that of the conventional transcritical refrigeration system. It is also found that both 45–55 °C low-grade heat and condensing heat could be used as actuating heat of the two-stage absorption refrigeration subsystem. Highlights: A novel absorption-transcritical hybrid refrigeration system is proposed. The thermodynamic models are established for the hybrid system. Main effects are discussed on performance of the hybrid system. This system could show great potential in utilization of low-grade heat.